High‐Intensity Telemedicine‐Enhanced Acute Care for Older Adults: An Innovative Healthcare Delivery Model. Issue 11 (28th October 2013) - Shah, Manish N.; Gillespie, Suzanne M.; Wood, Nancy; Wasserman, Erin B.; Nelson, Dallas L.; Dozier, Ann; McConnochie, Kenneth M.
<x xml:space="preserve">Abstract</x> Accessing timely acute medical care is a challenge for older adults. This article describes an innovative healthcare model that uses high‐intensity telemedicine services to provide rapid acute care for older adults without requiring them to leave their senior living community (SLC) residences. This program, based in a primary care geriatrics practice that cares for SLC residents, is designed to offer acute care through telemedicine for complaints that are felt to need attention before the next available outpatient visit but not to require emergency department (ED) resources. This option gives residents access to care in their residence. Measures used to evaluate the program include successful completion of telemedicine visits, satisfaction of residents and caregivers with telemedicine care, and site of care that would have been recommended had telemedicine been unavailable. During the first 2 years of the program's operation, 281 of 301 requested telemedicine visits were completed successfully. Twelve residents were sent to an ED for care after the telemedicine visit. Ninety‐four percent of residents reported being satisfied or very satisfied with telemedicine care. Had telemedicine not been available, residents would have been sent to an ED (48.1%) or urgent care center (27.0%) or been scheduled for an outpatient visit (24.4%). The project demonstrated that high‐intensity telemedicine services for acute illnesses are feasible and acceptable and can provide definitive care without requiring ED or urgent care use. Continuation of the program will require evaluation demonstrating equal or better resident‐level outcomes and the development of sustainable business models.